Swimming upregulates APOL3 through regulating macrophage polarization to inhibit glycolysis and the development of melanoma - Lyu, Zhenlei; Mahenderan, Appukutty; Radhakrishnan, Ammu Kutty G. K.; Chin, Yit Siew; Yin, Chao (Springer Science and Business Media Deutschland, 2024)
This study investigated the role of swimming exercise in regulating melanoma tumour growth and glycolysis in cancer cells, the specific mechanism involved was also studied. In our study, a murine melanoma tumour model was established to assess the impact of swimming on tumour growth. The mRNA and protein expressions were assessed using qRT-PCR, western blot, and IHC. The metabolic behavior of melanoma cells was examined through lactic acid level measurements and glucose consumption assessments. CCK-8 and colony formation assays were used to detect cell viability and proliferation. ELISA was employed to determine the levels of cytokines secreted by macrophages. The interaction between APOL3 and STAT3 was analyzed by dual luciferase reporter gene and ChIP assays. Our results demonstrated that swimming exercise suppressed melanoma growth in mice by suppressing glycolysis, which might be related to APOL3 upregulation. In addition, downregulation of APOL3 in melanoma was associated with poor prognosis, and APOL3 overexpression markedly suppressed melanoma cell proliferation by reducing glucose uptake and lactate production in vitro. Mechanistically, STAT3 directly down-regulated APOL3 transcription. Swimming upregulated APOL3 by inactivating the IL-6R-STAT3 signaling axis in melanoma cells by inhibiting the secretion of IL-6 by M2 macrophages. As expected, IL-6 secreted by M2 macrophages promoted glycolysis in melanoma cells by reducing APOL3 expression. In summary, swimming inactivated the IL-6R/STAT3 signaling axis in melanoma cells by inhibiting the secretion of IL-6 by M2 macrophages, which could suppress the growth of melanoma in the body by upregulating APOL3 to inhibit glycolysis.